Pengaruh Beban Kerja dan Stres Kerja terhadap Kinerja Karyawan PT. Prudential Life Assurance (MRT Stars Agency) - Dewi Novia Anggraini; Iswati Iswati; Arief Widijatmoko (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to determine how the influence of workload and work stress kerja on employee performance. This study uses a quantitative approach by taking the case at PT. Prudential Life Assurance (MRT Stars Agency). The sample in this study used a nonprobability sampling technique with a saturated sampling category, so that the sample of this study were 30 employees at the PT. Prudential Life Assurance (MRT Stars Agency). Data collection uses primary data and secondary data which is then analyzed using multiple linear regression analysis with an Adjusted R Square value of 0.847 or 84.7% with the help of the IBM SPSS software application. The results of this study indicate that the workload and work stress simultaneously affect employee performance.